Cranioplasty with outer table bone graft obtained without craniotomy - Viterbo, F.; Modenese, E.; Proteti, R.; Campos, E. (My University, 1989)
The authors report three cases of cranial reconstruction by outer table bone graft obtained without craniotomy. Indications and the usual cranioplasty procedures are discussed.